2019
DOI: 10.1016/j.bpj.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

VenusA206 Dimers Behave Coherently at Room Temperature

Abstract: Fluorescent proteins (FPs) have revolutionized cell biology by allowing genetic tagging of specific proteins inside living cells. In conjunction with Fö rster's resonance energy transfer (FRET) measurements, FP-tagged proteins can be used to study protein-protein interactions and estimate distances between tagged proteins. FRET is mediated by weak Coulombic dipole-dipole coupling of donor and acceptor fluorophores that behave independently, with energy hopping discretely and incoherently between fluorophores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…In 2019, further experimental evidence for room temperature coherent molecular interactions between FP fluorophores was obtained by Kim et al The study reported unexpected FP quantum behaviour resulting from excitonic coupling in homodimers of dimeric yellow fluorescent protein Venus A206 under physiological conditions (Figure 11A) [340]. Time-resolved fluorescence anisotropy measurements were used to reveal ultrafast energy transfer (defined as faster than the instrument response function of the anisotropy system, ~146 ps) between FP fluorophores when Venus A206 FPs dimerise (Figure 11B).…”
Section: Exciton Coupling In Homodimers Of Yellow Fluorescent Protein Venus A206mentioning
confidence: 83%
See 3 more Smart Citations
“…In 2019, further experimental evidence for room temperature coherent molecular interactions between FP fluorophores was obtained by Kim et al The study reported unexpected FP quantum behaviour resulting from excitonic coupling in homodimers of dimeric yellow fluorescent protein Venus A206 under physiological conditions (Figure 11A) [340]. Time-resolved fluorescence anisotropy measurements were used to reveal ultrafast energy transfer (defined as faster than the instrument response function of the anisotropy system, ~146 ps) between FP fluorophores when Venus A206 FPs dimerise (Figure 11B).…”
Section: Exciton Coupling In Homodimers Of Yellow Fluorescent Protein Venus A206mentioning
confidence: 83%
“…It was therefore thought to be highly unlikely that coherent energy transfer takes place between fluorescent proteins (FPs) as fluorophore proximity is limited by the FP β-barrel structure and, in a warm, wet biological environment, vibrational decoherence would rapidly intervene to obliterate quantum coherent molecular interactions. Nonetheless, evidence indicates that anomalous photophysical properties of FP have been observed at room temperature, which cannot be understood explicitly within the boundaries of classic physics [337][338][339][340][341][342][343][344][345][346]. Surprisingly, recent experimental evidence observing generation of photonic entanglement in enhanced green fluorescent protein (eGFP) [339] and exciton coupling between dimeric yellow fluorescent proteins, Venus, [340] strongly supports the hypothesis that FPs can interact coherently under physiological conditions.…”
Section: Fluorescent Protein As a Novel Model System For Quantum Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of these energy hops is k FRET . Under specialized conditions, a donor and acceptor can be so strongly coupled to each other that they no longer behave independently (Förster, 1965; Kasha, 1963; Kenkre & Knox, 1974; kim et al, 2019). While still being composed of two fluorophores, quantum mechanically they behave as a single quantum entity.…”
Section: Flim‐fretmentioning
confidence: 99%